An innovative LYP-shear link as damper to improve the behavior of reinforced concrete frames - Ghamari, Ali; Karimi, Imran; Drygala, Izabela; Putra Jaya, Ramadhansyah (Institution of Structural Engineers, 2025)
According to the experience gained from previous earthquakes, reinforced concrete (RC) frames are susceptible to damage although they have considerable advantages. Adding concentrically braced frames (CBFs) to the RC frames enhances strength and stiffness but reduces the ductility of the system. This shortcoming is due to the susceptibility of the diagonal elements of CBF to buckling. Subsequently, in this paper, an innovative metallic damper is investigated that it pertains to the simplicity of construction and implementation. Since adding the damper is expected to prevent buckling of the CBF elements and improve the dissipation imposed energy, it reduces the stiffness of the system. So, to overcome the problem, the web plate of the damper is made of low yield point steel (LYP) so that a thicker plate is used that does not increase the transformed stress from the damper to other parts of the structure. Results indicate that using the LYP-damper has a better performance than the conventional damper in terms of stiffness, ultimate strength, and dissipation energy. For both types of dampers, the reduction of the length-to-height ratio of the damper enhances the stiffness and strength and stiffness. Also, the required equation to design and predict the system is presented.